MENGANALISIS MAKNA NUBA NARA DALAM MASYARAKAT KOTENWALANG MELALUI PERSPEKTIF ANTROPOLOGI SIMBOLIK CLIFFORD GEERTZ - Sekosi, Eduardus (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2026)
This paper is motivated by the importance of understanding the symbolic meaning of traditions in local culture as part of community identity, specifically the Nuba Nara tradition in the culture of the Kotenwalang community, Tanjung Bunga District, East Flores Regency. Nuba Nara is a sacred place or space in the Kotenwalang community used to carry out traditional rituals. This term does not only refer to a physical location, but also contains deep symbolic meaning in the social and spiritual life of the Kotenwalang community. The purpose of this paper is to analyze the meaning of Nuba Nara through the perspective of Clifford Geertz's symbolic anthropology, which emphasizes the interpretation of cultural symbols in social life. The research method used is a qualitative method with a descriptive interpretative approach. This writing is motivated by local culture in Kotenwalang, Tanjung Bunga District, East Flores Regency. With the subjects of the writing include traditional leaders, local communities. The data collection technique was carried out through interviews via WhatsApp. The results of the writing show that Nuba Nara is not just a traditional ritual, but a symbol full of spiritual, social, and cultural meaning. This tradition represents the relationship between humans and their ancestors, strengthens social solidarity, and serves as a medium for transmitting cultural values. Through a symbolic anthropology perspective, Nuba Nara is understood as a system of symbols that gives meaning to the realities of life among the Kotenwalang people. As such, this tradition plays a crucial role in maintaining the continuity of local cultural identity amidst the tide of modernization.